Geomorfologi Pesisir Pantai Benteng Portugis, Kecamatan Donorojo, Kabupaten Jepara - Warsito Atmodjo (Universitas Diponegoro, 2016)
The dynamics of coastal geomorphology depending on the rock making up the coastal and oceanographic processes that work. Coastal geomorphology dynamic process influenced by oceanographic processes and can result in the accretion process and coastal erosion. This study aims to determine the dynamics of the process of coastal geomorphology and oceanographic factors that influence the process. This study uses the case with the analysis of dynamics of geomorphological and oceanographic processes that influence in the region penlitian. The research data in the form of tides, currents and sediments in coastal areas. The results of the study be a type of tidal Daily Single with water level Z0 = 55.90; (MSL) 69.14 cm; (HHWL) = 135.48 cm; (LLWL) = 0.78 cm. Waves as high as 0.62 meters and wave period 4.1 seconds. The waves come from the Northeast will burst burst as high as 0.81 meters at a depth of 0.78 meters. Breaking waves at an angle of 19.22 degrees to the shoreline, will result in flow velocity along the coast is 0.98 m / sec.Coastal geomorphology consists of rugged coastal hills of volcanic material composed of tuffaceous sand and clastic limestone and non clastics limestone and limestones; type of geomorphologys was coastal flat composed of silty sand; coastal river estuary composed of silty sand; coastal erosion occurs berm erosion. Geomorphology dynamic process influenced by longshore currents that cause abrasion dominant in the study area. Dinamika geomorfologi pesisir pantai tergantung pada batuan penyusun pesisir pantai dan proses oseanografi yang bekerja. Proses dinamika geomorfologi pesisir pantai di pengaruhi oleh proses oseanografi dan dapat berakibat terjadinya proses akresi dan erosi pesisir. Penelitian ini bertujuan mengetahui dinamika proses geomorfologi pesisir pantai dan proses faktor oseanografi yang berpengaruh. Penelitian ini menggunakan metode kasus dengan analisis dinamika proses geomorfologi dan oceanografi yang berpengaruh di daerah penlitian. Data penelitian berupa pasang surut, arus dan sedimen di wilayah pesisir pantai. Hasil penelitian berupa tipe pasang surut Harian Tunggal dengan elevasi muka air Z0 = 55,90; (MSL) 69,14 cm; (HHWL) = 135,48 cm; (LLWL) = 0,78 cm. Gelombang setinggi 0,62 meter dan periode gelombang 4,1 detik. Gelombang datang dari arah Timur Laut akan pecah pecah setinggi 0,81 meter pada kedalaman sebesar 0,78 meter. Gelombang pecah dengan sudut datang 19,22 derajat terhadap garis pantai, akan mengakibatkan kecepatan arus sepanjang pantai 0.98 m/detik. Geomorfologi pesisir terdiri dari pesisir pantai bukit terjal tersusun material volkanik pasir tufaan dan batu gamping klastik dan batu gamping non klastik; pesisir landai/datar tersusun pasir lanauan; pesisir pantai muara sungai tersusun oleh pasir lempungan; pesisir pantai erosi terjadi erosi berm. Proses dinamika geomorfologi dipenaruhi oleh arus longshore yang menyebabkan adanya dominan abrasi di daerah penelitian.